PENGARUH MODEL PEMBELAJARAN GENERATIVE MULTI REPRESENTATION LEARNING (GMRL) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA (JURNAL LEMMA, 2023)
AbstractThis research was conducted at SMP Atthayyibah, Semurup, Kerinci in 2020/2021. This study aims to determine difference in student’s problem solving abilities using Generative Multi Representation Learning (GMRL) models and conventional learning models. This type of research is quantitative using a quasi-experimental approach. The research sample consisted of 40 people consisting of 2 classes (VIII.A as the control class and VIII.B as the experimental class). This study used a posttest design only control group design. In the experimental class after treatment (GMRL learning process) and the control class with conventional learning processes, a problem solving ability test was carried out. The result showed that the problem solving abilities of students using the GMRL learning model were higher than those using conventional learning models. In conclusion, there are differences in students’ mathematical problem solving abilities using GMRL model in grade VIII SMP Attayyibah, Semurup, Kabupaten Kerinci in the 2020/2021 school year.